Plasma Klotho and Frailty in Older Adults: Findings From the InCHIANTI Study - Shardell, Michelle (J Gerontol A Biol Sci Med Sci, 2019)
BACKGROUND: The hormone klotho, encoded by the gene klotho, is primarily expressed in the kidney and choroid plexus of the brain. Higher klotho concentrations have been linked to better physical performance; however, it is unknown whether klotho relates to frailty status in older adults. METHODS: Plasma klotho was measured in 774 participants aged ≥65 years enrolled in InCHIANTI, a prospective cohort study comprising Italian adults. Frailty status was assessed at 3 and 6 years after enrollment. Frailty was defined as presence of at least three out of five criteria of unintentional weight loss, exhaustion, sedentariness, muscle weakness, and slow walking speed; prefrailty was defined as presence of one or two criteria; and robustness was defined as zero criteria. We assessed whether plasma klotho concentrations measured at the 3-year visit related to frailty. RESULTS: Each additional natural logarithm of klotho (pg/mL) was associated with lower odds of frailty versus robustness after adjustment for covariates (odds ratio [OR] 0.46; 95% confidence interval 0.21, 0.98; p-value = .045). Higher klotho was particularly associated with lower odds of exhaustion (OR 0.57; 95% CI 0.36, 0.89; p-value = .014). Participants with higher klotho also had lower estimated odds of weight loss and weakness, but these findings were not statistically significant. CONCLUSIONS: Higher plasma klotho concentrations were associated with lower likelihoods of frailty and particularly exhaustion. Future studies should investigate modifiable mechanisms through which klotho may affect the frailty syndrome.